Active ingredients screening and pharmacological mechanism research of curcumae rhizoma-sparganii rhizoma herb pair ameliorates liver fibrosis based on network pharmacology. (6th April 2023) - Hao, Min; Yao, Zhouhui; Zhao, Mengting; Chen, Ziyan; Wang, Pingping; Sang, Xianan; Yang, Qiao; Wang, Kuilong; Han, Xin; Cao, Gang
Abstract: Ethnopharmacological relevance: Curcumae Rhizoma-Sparganii Rhizoma (CR-SR) is a classic herbal pair to promote blood circulation and remove blood stasis in ancient China. However, the molecular mechanism is still unclear. Aim of study: To screen out the anti-liver fibrosis active ingredients in CR-SR. Moreover, preliminary exploration the molecular mechanism of CR-SR to ameliorates liver fibrosis. Materials and methods: In this research, plant taxonomy has been confirmed in the "The Plant List" database (www.theplantlist.org ). The chemical components of CR-SR were analysed by ultra-performance liquid chromatography-quadrupole/time-of-flight mass spectrometry (UPLC-Q/TOF-MS). "Component-Target-Pathway-Disease" network of CR-SR components were built by network pharmacology. Then, the interaction between primary components and predicted protein targets based on network pharmacology were validated by molecular docking. The pharmacological actions of CR-SR were verified by blood biochemical indexes, histopathologic examination of CCL4 induced rats' model. The core protein targets were verified by Western blot. The effects of screened active components by molecular autodocking were verified by HSC-T6 cell experiment. Results: The result shows that 57 chemical constituents in CR-SR herbal pair were identified by UPLC-Q/TOF-MS, in which, 27 compounds were closely connected with liver fibrosis related protein targets. 55 protein targets screened out by "component-target-pathway-disease network" maybe the underlying targets for CR-SR to cure liver fibrosis. Moreover, the 55 protein targets are mainly related to RNA transcription, apoptosis, and signal transduction. The molecular autodocking predicted that ten components can bond well with PTGS2 and RELA protein targets. The blood biochemical indexes, histopathologic examination of CCL4 induced rats experiment showed that CR-SR has well intervention effect of liver fibrosis. The Western blot analysis indicated that CR-SR could significantly inhibit RELA, PTGS2, IL-6, SRC, and AKT1 protein expression to exert the anti-fibrosis effect. The HSC-T6 cell experiment indicated that both formononetin (FNT) and curdione could significantly inhibit the activation of HSC and reduce the expression of PTGS2, and p-AKT1 which was accordance with the molecular autodocking results. Conclusion: This study proved the molecular mechanism of CR-SR multi-component and multi-target anti-liver fibrosis effect through mass spectrometry, network pharmacology, and western blotting technology. The research provides a theoretical evidence for the development and utilization of CR-SR herbal pair. Graphical abstract: Image 1 Highlights: This study has identified 55 primary components of CR-SR herb pair by UPLC-Q/TOF-MS. Establishment "Compound-Target-Pathway-Disease" Network of 57 components of CR-SR in treating liver fibrosis. Verified the anti-liver fibrosis pharmacological action of CR-SR by CCL4 induced hepatic fibrosis rats model. Verified the anti-liver fibrosis potential protein targets of CR-SR by western blot in vivo and in vitro.